2020
DOI: 10.1136/heartjnl-2020-317125
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography aortic valve calcium scoring for the assessment of aortic stenosis progression

Abstract: ObjectiveCT quantification of aortic valve calcification (CT-AVC) is useful in the assessment of aortic stenosis severity. Our objective was to assess its ability to track aortic stenosis progression compared with echocardiography.MethodsSubjects were recruited in two cohorts: (1) a reproducibility cohort where patients underwent repeat CT-AVC or echocardiography within 4 weeks and (2) a disease progression cohort where patients underwent annual CT-AVC and/or echocardiography. Cohen’s d-statistic (d) was compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
(9 reference statements)
0
14
2
Order By: Relevance
“…We should consider whether we have failed to detect an effect of the intervention because of insensitivity of the measurements of aortic stenosis progression or a lack of power. We set out to undertake a comprehensive assessment of aortic stenosis severity and progression using 3 complementary but distinctly independent methods: aortic valve calcium scoring, Doppler echocardiography, and 18 F-NaF PET-CT. Aortic valve calcium scoring and echocardiography are standard clinical tools used to assess disease severity, 24 , 36 , 37 and we were able to identify and quantify disease progression across all 3 trial treatment arms using both of these methods. We observed an overall rate of hemodynamic progression that is consistent with published series and trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We should consider whether we have failed to detect an effect of the intervention because of insensitivity of the measurements of aortic stenosis progression or a lack of power. We set out to undertake a comprehensive assessment of aortic stenosis severity and progression using 3 complementary but distinctly independent methods: aortic valve calcium scoring, Doppler echocardiography, and 18 F-NaF PET-CT. Aortic valve calcium scoring and echocardiography are standard clinical tools used to assess disease severity, 24 , 36 , 37 and we were able to identify and quantify disease progression across all 3 trial treatment arms using both of these methods. We observed an overall rate of hemodynamic progression that is consistent with published series and trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have recently examined the contemporary use of aortic valve calcium scoring for assessing disease progression and demonstrated that modest sample sizes, not dissimilar to our present study, are needed to detect the desired effect size sought here. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative evaluation of TTE can measure the internal anatomical structure and valve size of the heart in real time, but it is easily affected by the operator level and aortic valve calcification, so the measurement results of TTE are small. Doris et al [ 33 ] evaluated the severity of aortic stenosis in patients with aortic valve calcification by CT quantification (CT-AVC) and conducted a comparative study with echocardiography. The results showed that CT-AVC was reproducible and the measurement reproducibility became more standardized over time, with higher accuracy than echocardiography, which was similar to the results of this research.…”
Section: Discussionmentioning
confidence: 99%
“…Other interesting papers in this issue of Heart include a study by Doris and colleagues 4 showing that in adults with aortic stenosis CT quantitation of valve calcification is reproducible and In a study of patients undergoing atrial fibrillation (AF) ablation, Piccini and colleagues 6 found that almost 30% experienced recurrent atrial tachycardiac (AT) or AF within 3 months. However, although those without recurrent AT/AF had greater improvement in functional status, overall quality of life was similar in those with and without AT/AF recurrence.…”
mentioning
confidence: 99%